Metal ion coordination cross-linked solvent-resistant sulfonated poly(arylene ether sulfone) cation exchange membrane, preparation method and application thereof
Patent Information
- Application Number
- CN202611303265.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-23
AI Technical Summary
然而,现有金属配位改性研究仍存在以下不足:(1)金属离子选择局限于少数过渡金属,对不同金属离子的配位能力及其对膜内离子通道尺寸、微相分离结构的调控规律缺乏系统研究;(2)金属配位对膜耐溶剂性的提升机理尚不清晰,特别是配位结构与溶剂溶胀行为之间的内在关联缺少定量认识
[0028] (1) Excellent resistance to organic solvents: The SPAES membrane modified by metal ion coordination crosslinking still maintains its intact morphology after being immersed in strong polar organic solvents such as MeOH, DMF, and DMSO for 30 days, and the mass loss rate is controlled within 4.7% (based on SPAES-Cu). 2+ For example, the desalination rate in DMSO is only 3.8%, which is far better than unmodified SPAES membranes (which swell and even dissolve severely) and commercial CMX membranes (the desalination rate in DMSO drops sharply from 98% to 89%).
Smart Images

Figure CN122958735A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane separation material technology and resource utilization technology of high-salt organic wastewater. Specifically, it relates to a solvent-resistant cation exchange membrane with a three-dimensional network structure constructed by non-covalent coordination crosslinking of metal ions with -NH groups on the molecular chain of sulfonated polyarylene ether sulfone, as well as its preparation method and application. Background Technology
[0002] High-salinity wastewater treatment and resource recovery is a common challenge faced by industries such as chemical, power, metallurgy, and pharmaceutical. Electrodialysis (ED) technology is considered one of the important technologies for achieving desalination and resource recovery of high-salinity wastewater due to its advantages of low energy consumption and no secondary pollution. Ion exchange membranes (IEMs) are the core materials in the ED process, and their performance directly determines desalination efficiency, energy consumption, selectivity, and long-term operational stability.
[0003] Sulfonated polyarylene ether sulfone (SPAES) ion exchange membranes are widely used in fields such as electrical discharge machining (ED) due to their excellent ion conductivity and chemical stability. However, pure SPAES membranes have significant technical limitations: the molecular chains are bound together only by weak interactions such as van der Waals forces and hydrogen bonds, lacking a dense cross-linked network. This makes them prone to swelling or even dissolution in systems containing highly polar organic solvents such as DMSO, DMF, and NMP, leading to increased membrane resistance, ion channel deformation, and decreased selectivity. Furthermore, the membrane exhibits low regularity of ion transport channels and uneven pore size distribution, hindering the processing of Li. + / Na + / K + Monovalent cations and Mg 2+ The sieving accuracy of divalent cations is insufficient.
[0004] Currently, strategies to improve the solvent resistance and ion selectivity of SPAES membranes mainly include covalent crosslinking and inorganic filler blending. However, covalent crosslinking is complex and easily damages the polymer molecular structure, resulting in increased membrane brittleness after modification; inorganic filler blending is prone to problems such as filler agglomeration and interface defects, making it difficult to precisely control the aggregated structure within the membrane.
[0005] Metal coordination crosslinking, as a non-covalent modification strategy, has attracted attention in recent years. By constructing a three-dimensional network through the coordination of metal ions with active groups (such as -NH, imidazole, etc.) on polymer chains, the mechanical strength, solvent resistance, and ion selectivity of the membrane can be improved simultaneously under mild conditions. However, existing research on metal coordination modification still has the following shortcomings: (1) The selection of metal ions is limited to a few transition metals, and there is a lack of systematic research on the coordination ability of different metal ions and their regulation of the size of ion channels and microphase separation structure in the membrane; (2) The mechanism by which metal coordination improves the solvent resistance of the membrane is not yet clear, especially the intrinsic relationship between the coordination structure and the solvent swelling behavior lacks quantitative understanding. Summary of the Invention
[0006] To address the aforementioned technical problems in existing technologies, this invention breaks away from the traditional modification approach of covalent crosslinking and inorganic filler blending, proposing a solvent-resistant sulfonated polyarylether sulfone cation exchange membrane based on non-covalent coordination crosslinking of metal ions. The core innovation lies in:
[0007] (1) Controllable construction of coordination crosslinking networks: Utilizing the inherent -NH active groups on the SPAES molecular chain, through interaction with multivalent metal ions (Cu... 2+ Cr 3+ Fe 3+ Zn 2+ The coordination of polymer chains (e.g., α) constructs a non-covalent three-dimensional cross-linked network within the membrane. This network effectively restricts the free movement of polymer chains, inhibits the permeation and swelling of organic solvent molecules, and optimizes the hydrophilic / hydrophobic microphase separation structure within the membrane through cross-linked chain rearrangement.
[0008] (2) Precise control of ion transport channels: The difference in coordination strength between different metal ions and -NH groups can be used to systematically control the size of ion clusters within the membrane (SAXS characterization shows that the channel size can be controlled from 0.49 nm to 0.34 nm). By selecting appropriate types and amounts of metal ions, it is possible to control monovalent / divalent cations (K+, K+, and N+) within the membrane. + / Mg 2+ Na + / Mg 2+ Precise optimization of selective sieving.
[0009] (3) Synergistic improvement of solvent resistance and ion selectivity: The metal coordination crosslinking network inhibits the invasion of solvent molecules through physical crosslinking on the one hand, and enhances the size exclusion effect by reducing the size of ion channels on the other hand, thereby achieving simultaneous optimization of solvent resistance and ion sieving performance, solving the technical problem that traditional modification methods cannot take both into account.
[0010] To achieve the above objectives, the present invention adopts the following technical solution:
[0011] A metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfone cation exchange membrane includes a sulfonated polyarylene ether sulfone matrix and a metal coordination crosslinked network. The metal coordination crosslinked network is formed by at least one polyvalent metal ion and -NH active groups on the sulfonated polyarylene ether sulfone molecular chain through non-covalent coordination bonds. The metal coordination crosslinked network makes the ion transport channel size in the membrane smaller than that in the unmodified sulfonated polyarylene ether sulfone membrane.
[0012] Furthermore, the multivalent metal ions are selected from Cu. 2+ Cr 3+ Fe 3+ Zn 2+ At least one of them.
[0013] Furthermore, the metal coordination crosslinking network is composed of two different multivalent metal ions selected from Cu. 2+ / Cr 3+ Cu 2+ / Fe 3+ Cr 3+ / Fe 3+ Cu 2+ / Zn 2+ Cr 3+ / Zn 2+ or Fe 3+ / Zn 2+ Any combination.
[0014] Furthermore, the molar ratio of the two metal ions is 0.1:0.9 to 0.9:0.1.
[0015] Furthermore, the size of the intramembrane ion transport channel is 0.34–0.49 nm, and the size of the ion transport channel varies depending on the type of metal ion, based on Cu. 2+ <Cr 3+ < Fe 3+ < Zn 2+ The order increases sequentially.
[0016] Furthermore, the membrane is effective against K. + / Mg 2+ The selectivity was 10.20–19.35 for Na. + / Mg 2+ The selectivity is 4.84–9.54, and the selectivity is based on Cu. 2+ > Cr 3+ Fe 3+ > Zn 2+ The order decreases.
[0017] A method for preparing the metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfone cation exchange membrane, characterized by comprising the following steps:
[0018] S1: Synthesis of Aminated Polyarylether Sulfones (PAES)
[0019] Under nitrogen protection, 4,4'-difluorodiphenyl sulfone, 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and hexafluorobisphenol A were dissolved in N-methylpyrrolidone in a certain molar ratio. Potassium carbonate was used as a salting agent, and the mixture was reacted at 145°C for 4 h. The temperature was then raised to 165°C and the reaction was continued for 3 h. After cooling, the mixture was precipitated in isopropanol, washed, and dried under vacuum to obtain the PAES polymer.
[0020] S2: Synthesis of sulfonated polyarylene ether sulfones (SPAES)
[0021] The PAES polymer was dissolved in N-methylpyrrolidone, and 1,3-propanesulfonic acid lactone was added. The mixture was reacted at 70°C for 12–15 h. After cooling, the precipitate was formed in isopropanol, washed repeatedly with deionized water, and dried under vacuum to obtain the SPAES polymer.
[0022] S3: General Casting Solution Preparation and Film Formation Process
[0023] The SPAES polymer was dissolved in NMP and stirred at room temperature until completely dissolved to obtain a homogeneous SPAES mother liquor.
[0024] The NMP solution of metal ions was added dropwise to the SPAES mother liquor and stirred evenly at room temperature to obtain the M-SPAES metal coordination casting solution.
[0025] After degassing the casting solution, it is cast onto a glass substrate and vacuum dried at 80°C for 15 h. After drying, it is peeled off to obtain the metal ion coordination crosslinked sulfonated polyarylether sulfone ion membrane.
[0026] The application of the metal ion coordination crosslinked solvent-resistant sulfonated polyarylether sulfone cation exchange membrane in electrodialysis.
[0027] Compared with the prior art, the specific beneficial effects of the present invention are as follows:
[0028] (1) Excellent resistance to organic solvents: The SPAES membrane modified by metal ion coordination crosslinking still maintains its intact morphology after being immersed in strong polar organic solvents such as MeOH, DMF, and DMSO for 30 days, and the mass loss rate is controlled within 4.7% (based on SPAES-Cu). 2+ For example, the desalination rate in DMSO is only 3.8%, which is far better than unmodified SPAES membranes (which swell and even dissolve severely) and commercial CMX membranes (the desalination rate in DMSO drops sharply from 98% to 89%).
[0029] (2) Controllable ion channel size and selectivity: By selecting different metal ions, the size of the ion channels within the membrane can be systematically controlled in the range of 0.34–0.49 nm (SAXS characterization). The channel size is determined according to Cu. 2+ <Cr 3+ < Fe 3+ < Zn 2+ The order increases with the coordination strength of the metal ion -NH (Cu) 2+ > Cr 3+ Fe 3+ > Zn 2+ The negative correlation between coordination strength, channel size, and ion selectivity reveals the intrinsic relationship between coordination strength and ion selectivity. Among them, SPAES-Cu... 2+The membrane channel size is the smallest (0.34 nm), corresponding to the highest K+ / Mg ratio. 2+ Selectivity (19.35) and Na+ / Mg2+ selectivity (9.54); SPAES-Zn 2+ The membrane channel size is the largest (0.49 nm), corresponding to the lowest selectivity (K0). + / Mg 2+ is 10.20, Na + / Mg 2+ (4.84). The selectivity of each membrane was significantly better than that of commercial CIMS membranes (K). + / Mg 2+ Approximately 1.0, Na+ / Mg 2+ Approximately 1.07).
[0030] (3) Synergistic optimization of solvent resistance and separation performance: The metal coordination crosslinking network maintains low membrane resistance (2.8−4.1 Ω·cm) while suppressing solvent swelling. 2 With its high desalination rate (maintaining >96% even in a 50% DMSO system), it shows promising application prospects in the treatment of high-salt wastewater containing organic solvents.
[0031] (4) The preparation process is simple and the conditions are mild: metal ions are introduced by drop addition and the coordination reaction is completed at room temperature or <80℃. No toxic crosslinking agent is required and the amount of metal ions used is small (0.02−0.1 mol / kg). It is compatible with existing solution casting production lines and is easy to scale up industrially.
[0032] (5) Extensibility of bimetallic synergistic coordination: Based on the study of the single-metal system of this invention, it was found that there are significant differences in the coordination strength between different metal ions and the -NH group (the shift of the -NH characteristic peak in the FTIR spectrum is calculated according to Cu). 2+ > Cr 3+ >Fe 3+ > Zn 2+ The order of coordination strength decreases, and the difference in coordination strength directly determines the size of the intramembrane ion channels (SAXS characterization shows that the channel size increases from SPAES-Zn). 2+ 0.49 nm to SPAES-Cu 2+ The 0.34 nm system is tunable) and the selectivity for monovalent / divalent ions (K + / Mg 2+ Selective Cu 2+ > Cr 3+ Fe 3+ > Zn 2+ (in decreasing order) – it is reasonable to expect that by introducing two metal ions with different coordination abilities to construct a bimetallic coordination network, it is possible to utilize “strongly coordinating ions (such as Cu)”. 2+ or Cr3+ "Constructing a dense primary network" and "weakly coordinating ions (such as Zn)" 2+ The synergistic effect of "filling network gaps as a space regulator" further optimizes network density and ion sieving accuracy. Those skilled in the art can optimize membrane performance on demand by adjusting the type and ratio of bimetals according to the specific needs of the target separation system. Attached Figure Description
[0033] Figure 1 The metal ions in this invention (in the form of Cu) 2+ (For example) A schematic diagram of the structure in which the -NH group on the SPAES molecular chain undergoes coordination crosslinking;
[0034] Figure 2a and Figure 2b For PAES, SPAES, and SPAES-M n+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ Fourier transform infrared (FTIR) spectrum of cation exchange membrane, in which Figure 2a 4000-500 cm −1 Full spectrum Figure 2b 2000–400 cm −1 Local magnification spectra are used to characterize the shift and peak width changes of the -NH characteristic peak, verifying the coordination effect between metal ions and -NH groups.
[0035] Figure 3 For SPAES-M n+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ Scanning electron microscope (SEM) images of cation exchange membranes, where (a-d) represent surface morphology and (e-h) represent cross-sectional morphology, used to observe changes in the surface and internal microstructure of the membrane before and after metal ion coordination.
[0036] Figure 4a and Figure 4b They are SPAES and SPAES-M respectively. n+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ Small-angle X-ray scattering (SAXS) spectra and ion channel size statistics of cation exchange membranes are used to characterize the regulatory mechanism of different metal ion coordination on the size of ion clusters within the membrane.
[0037] Figure 5a and Figure 5b They are SPAES and SPAES-M respectively. n+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ Transmission electron microscopy (TEM) images and water contact angle histograms of cation exchange membranes are used to characterize the microphase separation structure and changes in surface hydrophilicity within the membrane.
[0038] Figures 6a-6d For SPAES-M n+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ Figure 1 shows the results of solvent absorption and swelling rate tests of cation exchange membranes in water, 50% MeOH (aq.), 50% DMF (aq.), and 50% DMSO (aq.).
[0039] Figure 7a and Figure 7b For SPAES-M n+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ Macroscopic morphology photographs and membrane resistance change graphs of cation exchange membranes after immersion in MeOH, DMF, and DMSO for 30 days.
[0040] Figures 8a-8e For SPAES-M n+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ The diagram shows the desalination performance of cation exchange membranes during electrodialysis. Figure 8a and Figure 8b The changes in conductivity and desalination rate in 0.5 M NaCl aqueous solution. Figure 8c and Figure 8d The changes in conductivity and desalination rate in a 50% DMSO (aq.) system. Figure 8e The results are the desalination stability test results of a 50% DMSO (aq.) system for eight consecutive cycles.
[0041] Figure 9a and Figure 9b For SPAES-Mn+ (M) n+ = Cu 2+ Cr 3+ Fe 3+ Zn 2+ The ion selectivity diagram of cation exchange membranes during electrodialysis, where... Figure 9a For K + and Mg 2+ Concentration changes and K + / Mg 2+ Selectivity Figure 9b for Na + and Mg 2+ Concentration changes and Na + / Mg 2+ Selectivity was assessed and compared with commercial CIMS membranes. Detailed Implementation
[0042] To more clearly illustrate the technical solution and advantages of the present invention, the present invention will be described in detail below with reference to embodiments. It should be noted that the implementation methods of the present invention are not limited to the following embodiments; the following embodiments are only used to explain the technical solution of the present invention and do not constitute a limitation of the present invention.
[0043] The method for preparing the metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfone cation exchange membrane of the present invention includes the following steps:
[0044] S1: Synthesis of Aminated Polyarylether Sulfones (PAES)
[0045] Under nitrogen protection, 4,4'-difluorodiphenyl sulfone, 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and hexafluorobisphenol A were dissolved in N-methylpyrrolidone at a certain molar ratio (preferably 40:28:12), with potassium carbonate as the salting agent. The reaction was carried out at 145°C for 4 h, and then the temperature was raised to 165°C for another 3 h. After cooling, the product was precipitated in isopropanol, washed, and dried under vacuum to obtain PAES polymer.
[0046] S2: Synthesis of sulfonated polyarylene ether sulfones (SPAES)
[0047] PAES was dissolved in N-methylpyrrolidone, and 1,3-propanesulfonic acid lactone (in excess relative to the molar ratio of amino groups in PAES, preferably 2–5 times molar excess) was added. The mixture was reacted at 70°C for 12–15 h. After cooling, the precipitate was formed in isopropanol, washed repeatedly with deionized water, and dried under vacuum to obtain the SPAES polymer.
[0048] General casting solution preparation and film formation process
[0049] Weigh 0.9 g of SPAES and dissolve it in 15 mL of NMP. Stir at room temperature until completely dissolved to obtain a homogeneous SPAES mother liquor.
[0050] Take 2 mL of NMP solution corresponding to the metal ion (see each example for specific concentration), add it dropwise to 13 mL of SPAES mother liquor, stir evenly at room temperature to obtain 15 mL of M-SPAES metal coordination casting solution;
[0051] After degassing the casting solution, it was cast onto a glass substrate and dried under vacuum at 80°C for 15 h. After drying, it was peeled off to obtain a metal ion coordination crosslinked sulfonated polyarylene ether sulfone ion membrane (M-SPAES CEM).
[0052] Example 1 (Cu) 2+ Coordination modification)
[0053] Variable: Metal ion is Cu 2+ Using CuCl2 as raw material, prepare 2 wt% Cu 2+ / NMP solution.
[0054] Preparation method:
[0055] Weigh 0.9 g of SPAES and dissolve it in 13 mL of NMP. Stir at room temperature for 5 h until completely dissolved. Measure 2 mL of 2 wt% Cu... 2+ / NMP solution was added dropwise to SPAES solution, and stirred at room temperature for 10 min. After degassing, the mixture was cast onto a glass substrate, dried under vacuum at 80°C for 24 h, and then peeled off to obtain SPAES-Cu. 2+ Cation exchange membrane. The obtained membrane was acidified by immersing it in 1 mol / L H2SO4 solution for 24 h, and then washed with deionized water until neutral.
[0056] Structure and performance:
[0057] FTIR: The characteristic peak of -NH is at 3361 cm⁻¹ −1 Displaced to 3391 cm −1 The peak width increased significantly, indicating that Cu 2+ It coordinates with the -NH group.
[0058] SAXS: The ion channel size within the membrane is 0.34 nm (calculated from the scattering vector q), which is the smallest among the four metal ion modified membranes.
[0059] SEM / EDS: The membrane surface is smooth and dense, and Cu is uniformly distributed within the membrane, confirming Cu... 2+ The successful introduction of [the technology / mechanism].
[0060] Contact angle: 60.1°, significantly lower than that of pure SPAES membrane (76°), indicating improved hydrophilicity.
[0061] Membrane resistance (R) NaCl ): 2.8 ± 0.5 Ω·cm 2 (Tested in 0.5 M NaCl solution).
[0062] Ion exchange capacity (IEC): 1.88 ± 0.7 mmol·g −1 .
[0063] Solvent swelling ratio: 1.8% in 50% DMSO, 3.7% in 50% DMF, and 1.2% in 50% MeOH (all significantly lower than pure SPAES membranes).
[0064] Mass loss rate (30-day immersion): 3.8% in DMSO, 3.4% in DMF, and 1.7% in MeOH.
[0065] ED desalination rate: 99.34% in 0.5 M NaCl aqueous solution; still 96.27% after 24 h pre-soaking in 50% DMSO system.
[0066] Ion selectivity: K + / Mg 2+ Selectivity was 19.35, Na + / Mg 2+ Selectivity was 9.54 (current density 2.5 mA·cm). −2 ).
[0067] Characteristics: Cu 2+ It exhibits the highest coordination strength with the -NH group, forms the densest cross-linked network, and has the smallest ion channel size (0.34 nm), thus possessing the best mono / divalent ion selectivity and the best solvent resistance.
[0068] Example 2 (Cr) 3+ Coordination modification)
[0069] Variable: Metal ion is Cr 3+ A 2 wt% Cr3+ / NMP solution was prepared using CrCl3·6H2O as the raw material.
[0070] Preparation method: Referring to Example 1, Cu 2+ The solution was replaced with an equal volume of 2 wt% Cr 3+ / NMP solution.
[0071] Structure and performance:
[0072] FTIR: The characteristic peak of -NH is at 3361 cm⁻¹−1 Displaced to 3383 cm −1 The peak width increases.
[0073] SAXS: The intramembrane ion channel size is 0.35 nm.
[0074] SEM / EDS: The membrane surface is smooth and dense, and the Cr element is evenly distributed.
[0075] Contact angle: 64.8°.
[0076] Membrane resistance (R) NaCl ): 3.1 ± 0.2 Ω·cm 2 .
[0077] Ion exchange capacity (IEC): 1.85 ± 0.5 mmol·g −1 .
[0078] Solvent swelling ratio: 2.4% in 50% DMSO, 3.8% in 50% DMF, and 1.7% in 50% MeOH.
[0079] Mass loss rate (30-day immersion): 4.3% in DMSO, 3.9% in DMF, and 2.4% in MeOH.
[0080] ED desalination rate (50% DMSO system): approximately 95.8%.
[0081] Ion selectivity: K + / Mg 2+ Selectivity was 16.43, Na + / Mg 2+ The selectivity is 8.47.
[0082] Characteristics: Cr 3+ The coordination strength with the -NH group is second only to Cu. 2+ It has an ion channel size of 0.35 nm and excellent overall performance.
[0083] Example 3 (Fe) 3+ Coordination modification)
[0084] Variable: Metal ion is Fe 3+ Using FeCl3 as raw material, a 2 wt% Fe 3+ / NMP solution.
[0085] Preparation method: Referring to Example 1, Cu 2+ The solution was replaced with an equal volume of 2 wt% Fe. 3+ / NMP solution.
[0086] Structure and performance:
[0087] FTIR: The characteristic peak of -NH is at 3361 cm⁻¹ −1 Displaced to 3379 cm −1 .
[0088] SAXS: The intramembrane ion channel size is 0.48 nm.
[0089] SEM / EDS: The membrane surface is smooth and dense, and the Fe element is evenly distributed.
[0090] Contact angle: 71.5°.
[0091] Membrane resistance (R) NaCl ): 3.5 ± 0.4 Ω·cm 2 .
[0092] Ion exchange capacity (IEC): 1.83 ± 0.7 mmol·g −1 .
[0093] Solvent swelling ratio: 2.8% in 50% DMSO, 4.2% in 50% DMF, and 2.1% in 50% MeOH.
[0094] Mass loss rate (30-day immersion): 4.5% in DMSO, 4.2% in DMF, and 2.9% in MeOH.
[0095] ED desalination rate (50% DMSO system): approximately 95.3%.
[0096] Ion selectivity: K + / Mg 2+ Selectivity was 14.25, Na + / Mg 2+ The selectivity is 6.50.
[0097] Characteristics: Fe 3+ The coordination strength with the -NH group is moderate, and the ion channel size is 0.48 nm.
[0098] Example 4 (Zn) 2+ Coordination modification)
[0099] Variable: Metal ion is Zn 2+ Using ZnCl2 as raw material, a 2 wt% Zn 2+ / NMP solution.
[0100] Preparation method: Referring to Example 1, Cu 2+ The solution was replaced with an equal volume of 2 wt% Zn. 2+ / NMP solution.
[0101] Structure and performance:
[0102] FTIR: The characteristic peak of -NH is at 3361 cm⁻¹ −1 Displaced to 3373 cm −1 .
[0103] SAXS: The intramembrane ion channel size is 0.49 nm.
[0104] SEM / EDS: The membrane surface is smooth and dense, and the Zn element is evenly distributed.
[0105] Contact angle: 72.4°.
[0106] Membrane resistance (R) NaCl ): 4.1 ± 0.2 Ω·cm 2 .
[0107] Ion exchange capacity (IEC): 1.80 ± 0.6 mmol·g −1 .
[0108] Solvent swelling ratio: 3.7% in 50% DMSO, 4.9% in 50% DMF, and 2.9% in 50% MeOH.
[0109] Mass loss rate (30-day immersion): 4.7% in DMSO, 4.6% in DMF, and 3.5% in MeOH.
[0110] ED desalination rate (50% DMSO system): approximately 94.9%.
[0111] Ion selectivity: K + / Mg 2+ Selectivity is 10.20, Na + / Mg 2+ The selectivity is 4.84.
[0112] Characteristics: Zn 2+ It has the weakest coordination strength with the -NH group among the four metal ions, the largest ion channel size (0.49 nm), and the lowest selectivity and solvent resistance.
[0113] Comparative Example 1 (pure SPAES membrane)
[0114] Process: No metal ions are added; the film is cast directly using SPAES mother liquor. The remaining processing steps are the same as in Example 1.
[0115] performance:
[0116] FTIR: The characteristic peak of -NH is located at 3361 cm⁻¹ −1 No displacement.
[0117] SAXS: The intramembrane ion channel size is 0.50 nm.
[0118] Contact angle: 76°.
[0119] Membrane resistance (R) NaCl ): 1.5 ± 0.3 Ω·cm 2 .
[0120] Ion exchange capacity (IEC): 1.93 ± 0.8 mmol·g −1 .
[0121] Solvent swelling ratio: approximately 12.5% in 50% DMSO (the membrane becomes noticeably softer), approximately 11.2% in 50% DMF, and approximately 6.1% in 50% MeOH.
[0122] Mass loss rate (30-day immersion): >15% in DMSO (dissolution at the membrane edge), approximately 12% in DMF, and approximately 5% in MeOH.
[0123] ED desalination rate (water system): approximately 98.1%; (50% DMSO system): <80%, due to membrane structure damage.
[0124] Ion selectivity (aqueous system): K + / Mg 2+ Approximately 5.
[0125] Characteristics: No cross-linked network, extremely poor solvent resistance, significant swelling or even dissolution in highly polar organic solvents, and low selectivity.
[0126] Comparative Example 2 (Commercial Membrane CIMS)
[0127] Processing: Perform pretreatment activation according to the manufacturer's recommended method.
[0128] Performance (compared to this invention):
[0129] Film resistance: approximately 3.2 Ω·cm 2 .
[0130] After soaking in 50% DMSO for 24 hours: the membrane swelled significantly and some of its structure was damaged.
[0131] ED desalination rate (water system): approximately 97%; (50% DMSO system): approximately 89%, showing a significant decrease.
[0132] Ion selectivity: K + / Mg 2+ Approximately 1.0, Na + / Mg 2+ It is approximately 1.07.
[0133] Characteristics: Commercial membranes are not resistant to strongly polar organic solvents, their performance drops significantly in systems containing DMSO, and they exhibit extremely low selectivity.
[0134] Comparative Example 3 (Physical Mixing Control – Non-Coordinated Metal Salt)
[0135] Process: Refer to the film-forming process of Example 1, but replace CuCl2 with an equimolar amount of NaCl (Na + (Cannot form a coordinate bond with -NH group).
[0136] Structure and performance:
[0137] FTIR: The characteristic peak of -NH is located at 3361 cm⁻¹ −1 No displacement (consistent with pure SPAES), confirming Na + It did not coordinate with the -NH group.
[0138] SAXS: The ion channel size within the membrane is approximately 0.49–0.50 nm (close to that of a pure SAXS membrane).
[0139] Solvent swelling ratio: approximately 11.5% in 50% DMSO, close to that of pure SPAES membranes.
[0140] ED desalination rate (50% DMSO system): approximately 82%, close to that of pure SPAES membrane.
[0141] Characteristics: This comparative example demonstrates that, without coordination crosslinking, physical mixing of metal salts alone cannot improve the solvent resistance and selectivity of the membrane. Improvement in membrane performance must rely on non-covalent coordination crosslinking between metal ions and -NH groups.
[0142]
[0143] Table 1 shows the preparation process and performance of each embodiment and control example.
Claims
1. A metal ion coordination crosslinked solvent-resistant sulfonated polyarylether sulfonate cation exchange membrane, characterized in that, It includes a sulfonated polyarylene ether sulfone matrix and a metal coordination crosslinking network, wherein the metal coordination crosslinking network is formed by at least one multivalent metal ion and the -NH active group on the sulfonated polyarylene ether sulfone molecular chain through non-covalent coordination bonds; the metal coordination crosslinking network makes the size of the ion transport channels in the membrane smaller than that of the unmodified sulfonated polyarylene ether sulfone membrane.
2. The metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfonate cation exchange membrane according to claim 1, characterized in that, The multivalent metal ions are selected from Cu. 2+ Cr 3+ Fe 3+ Zn 2+ At least one of them.
3. The metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfonate cation exchange membrane according to claim 2, characterized in that, The metal coordination crosslinking network is composed of two different multivalent metal ions selected from Cu. 2+ / Cr 3+ Cu 2+ / Fe 3+ Cr 3+ / Fe 3+ Cu 2+ / Zn 2+ Cr 3+ / Zn 2+ or Fe 3+ / Zn 2+ Any combination.
4. The metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfonate cation exchange membrane according to claim 3, characterized in that, The molar ratio of the two metal ions is 0.1:0.9 to 0.9:0.
1.
5. The metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfonate cation exchange membrane according to any one of claims 1-4, characterized in that, The size of the intramembrane ion transport channel is 0.34–0.49 nm, and the size of the ion transport channel varies depending on the type of metal ion. For Cu... 2+ <Cr 3+ < Fe 3+ < Zn 2+ The order increases sequentially.
6. The metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfonate cation exchange membrane according to any one of claims 1-4, characterized in that, The membrane pair K + / Mg 2+ The selectivity was 10.20–19.35 for Na. + / Mg 2+ The selectivity is 4.84–9.54, and the selectivity is based on Cu. 2+ > Cr 3+ Fe 3+ > Zn 2+ The order decreases.
7. A method for preparing a metal ion coordination crosslinked solvent-resistant sulfonated polyarylene ether sulfonate cation exchange membrane according to claim 1, characterized in that... Including the following steps: S1: Synthesis of Aminated Polyarylether Sulfones (PAES) Under nitrogen protection, 4,4'-difluorodiphenyl sulfone, 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and hexafluorobisphenol A were dissolved in N-methylpyrrolidone in a certain molar ratio. Potassium carbonate was used as a salting agent, and the mixture was reacted at 145°C for 4 h. The temperature was then raised to 165°C and the reaction was continued for 3 h. After cooling, the mixture was precipitated in isopropanol, washed, and dried under vacuum to obtain the PAES polymer. S2: Synthesis of sulfonated polyarylene ether sulfones (SPAES) The PAES polymer was dissolved in N-methylpyrrolidone, and 1,3-propanesulfonic acid lactone was added. The mixture was reacted at 70°C for 12–15 h. After cooling, the precipitate was formed in isopropanol, washed repeatedly with deionized water, and dried under vacuum to obtain the SPAES polymer. S3: General Casting Solution Preparation and Film Formation Process The SPAES polymer was dissolved in NMP and stirred at room temperature until completely dissolved to obtain a homogeneous SPAES mother liquor. The NMP solution of metal ions was added dropwise to the SPAES mother liquor and stirred evenly at room temperature to obtain the M-SPAES metal coordination casting solution. After degassing the casting solution, it is cast onto a glass substrate and vacuum dried at 80°C for 15 h. After drying, it is peeled off to obtain the metal ion coordination crosslinked sulfonated polyarylether sulfone ion membrane.
8. The application of the metal ion coordination crosslinked solvent-resistant sulfonated polyarylether sulfone cation exchange membrane according to claim 1 in electrodialysis.